Fabrication of catalyst–coated membrane (CCM) for proton exchange membrane fuel cells - Dhanabal, Dashen (2019)
Traditional power generation devices depend on primary energy sources such as oil and coal to convert them into useful electrical energy. Apart from providing useful energy, these methods also contribute to harmful emissions and damage the environment we are living in. Fortunately, Proton Exchange Membrane Fuel Cells have surfaced as a prime choice due to its compact configuration, ability to operate in room temperature and its high efficiency. The catalyst coated membrane, CCM, plays a key role in converting hydrogen into electrical energy. Each membrane is subjected to processing conditions such as base temperature, nozzle flowrate as well as the post treatment pressure. A change in these conditions can have an impact on the performance of a fuel cell In this project, the main objective is to produce a catalyst coated membrane by altering different process conditions to produce the optimum performance.